ANALISIS KINERJA EKONOMI USAHA KELINCI PEDAGING DI KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Pratama, Rizky Aditya; Wakhidati, Yusmi Nur; Hidayat, Nunung Noor (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The purpose of the study is to determine the amount of investment, operational costs, and get the revenue for broiler rabbit business. To analyze the economic performance of the broiler rabbit business in terms of income and business efficiency. Knowing the effect of independent variables such as number of the ownership (X1), length of rearing (X2), the education of the breeder (X3), the number of family members (X4) and the type of rabbit (D) on the dependent variable, the income (Y1) and for the business efficiency as well (Y2). Materials and methods The target of this research is for the broiler rabbit breeders and the businessman as well in Baturraden District, Banyumas Regency. The location of the research was selected by using the technique of purposive sampling. The determination of the corespondents is done by Quota Sampling and there were 30 farmers selected. The data that has taken is the data for the last one year. The primary data was obtained by doing the observations and doing an interview to the farmers by using a list of questions, while the secondary data was obtained from the Central Statistics Agency of Banyumas Regency (2020). The analysist coefficient for determination shows the effect of the independent variable (X) on income (Y1) and business efficiency (Y2), respectively 76,7% and 24,5%. Results. The results of the F test, the independent variable (X) has a very significant effect on income (Y1), while the business efficiency (Y2) has no significant effect. The results of the t-test on income (Y1) is influenced by the number of the ownership (X1) and length of rearing (X2), while business efficiency (Y2) is influenced by the number of ownership (X1). Conclusion. The multiple linear regression equation systematically obtained is the income (Y1) = -1900,069 + 25,706X1 - 710,558X2 - 89,004X3 + 754,036X4 + 1398,153D + 7296,937 and the business efficiency (Y2) = 0,783 + 0,001X1 - 0,014X2 + 0,024X3 + 0,025X4 - 0,075D + 0,289.